A Review Learning Media Development Model - Saluky; Marine, Yoni (International Journal of Technology and Modeling, 2022)
This study aims to review various models of ICT-based learning media development. This study covers several development models such as ADDIE, SAM, RADD, Agile Development Model, Spiral Model, and DADD. The purpose of this research is to evaluate the advantages and disadvantages of each model and provide the best recommendations for the development of effective and efficient learning media. The results of this study are expected to contribute to the development of ICT-based learning media in the future.